Street dancing enhances cognitive reserve in young females: an fNIRS study - Wang, Yongbo; Zheng, Quansheng; Han, Yanbai; Fan, Yaqing; Liu, Hongen; Wang, Hongli (Frontiers in Neuroscience, 2025)
IntroductionWith the accelerating aging population, cognitive decline and dementia pose major public health challenges. Early intervention is crucial for mitigating these risks. Dance, with its high cognitive demands and multitasking coordination, has shown benefits for cognitive function. However, evidence on the effects of street dance on prefrontal cortex activation and executive function is limited. This study uses functional near-infrared spectroscopy (fNIRS) to explore how street dance impacts prefrontal activation and executive function, offering insights into early prevention of cognitive decline.MethodsA total of 28 healthy female college students were recruited and randomly assigned to a street dance intervention group (n = 14) or a control group (n = 14). The study was conducted between March and September 2024 at a university in Southwest China. The intervention group participated in an 18-week street dance program, three times per week, with each session lasting 80 min. The control group maintained their usual routines without structured physical activity. fNIRS was used pre- and post-intervention to assess changes in oxygenated hemoglobin (HbO₂) levels in the prefrontal cortex during the 2-back, Stroop, and More-Odd Shifting tasks.ResultsTwo-way repeated-measures ANOVA revealed significant Group × Time interaction effects in multiple prefrontal regions across the three tasks. In the 2-back task, the street dance group showed significant increases in HbO₂ in the right dorsolateral prefrontal cortex, accompanied by improvements in accuracy and faster reaction times. In the Stroop task, HbO₂ significantly increased in the right frontopolar and dorsolateral prefrontal cortices, reflecting enhanced inhibitory control. In the More-Odd Shifting task, significant activation was observed in the left inferior frontal gyrus, together with improved task-switching accuracy and reduced reaction times.ConclusionThe 18-week street dance intervention effectively improved working memory, inhibitory control, and cognitive flexibility, contributing to enhanced cognitive reserve. As a physical activity combining rhythm and coordination, street dance offers a promising early intervention strategy for delaying cognitive decline and reducing dementia risk.Clinical trial registrationhttps://www.chictr.org.cn/, identifier ChiCTR2400083689.